Tool wear mechanisms and surface quality assessment during micro-milling of high entropy alloy FeCoNiCrAlx. (February 2023) - Liang, Xiaoliang; Zhang, Canbin; Wang, Chunjin; Li, Kangsen; Loh, Yee Man; Cheung, Chi Fai
Abstract: High entropy alloys (HEA) are widely used in high-strength tools, high-temperature molds, and corrosion-resistant components. This work focused on tool wear and surface quality during micro-milling HEA FeCoNiCrAl x ( x = 0.1, 0.5, 1) with different Al element content. Tool wear appeared more severe with the increase of Al element content. Tool wear patterns mainly included flank wear, adhesive material, micro-chipping, coating peeling, substrate tearing and edge fracture. The combined effects of adhesive wear, mechanical shock damage, abrasive wear, and oxidative wear were the primary reasons of tool wear mechanisms, while the diffusion wear was less noticeable. Moreover, the surface qualities including surface roughness, surface defects and edge burrs changed worse with the increase of Al element content and tool wear. Graphical Abstract: ga1 Highlights: Tool wear and surface quality were investigated during micro-milling HEA FeCoNiCrAl x . Tool wear patterns included flank wear, adhesive material, micro-chipping, coating peeling, substrate tearing and edge fracture. Wear mechanisms including adhesion, mechanical shock damage, abrasion, oxidation, and diffusion were analysed. Surface qualities including surface roughness, surface defects and edge burrs were evaluated.